Kinetics of hematological and biochemical biomarkers are key tools for monitoring disease progression in Marburg virus-infected patients in Rwanda - Mugisha, Jean Claude; Kayigi, Etienne; Gahamanyi, Noel; Uwayo, Henri Desire; Umwanankabandi, Fidele; Gashema, Pierre; Rwagasore, Edison; Turatsinze, David; Nkeshimana, Menelas; Gashegu, Misbah; Ntagwabira, Edward; Makayoto, Lyndah; et al. (Scientific reports, 2025)
Marburg Virus Disease (MVD) is a severe disease with a fatality rate of up to 90%. Limited studies have suggested hematological and biochemical biomarkers for managing MVD, but data on key markers correlated with MVD development are scarce. This study aimed to investigate the biosignatures that can be used to monitor MVD progression in Marburg virus (MARV)-infected patients. We performed a retrospective analysis of biochemical and hematological data collected from 51 MARV-infected patients in Rwanda. The study subjects were classified according to the day of discharge: early (< 5 days), middle (5–10 days) and late recovery (> 10 days). Our data revealed that Aspartate transaminase (AST), Alanine transaminase (ALT)), and creatinine were significantly lower in MVD-recovered subjects as compared to newly admitted patients ( p < 0.0001 each). Lymphocytes and platelets were increased in MVD-recovered subjects ( p < 0.0001 and p < 0.001, respectively). ALT levels discriminated between middle, late recovered individuals, and MVD patients (AUC: 0.86, 0.90, 0.94, respectively). AST also showed strong discriminatory power for middle, late recovery, and MVD patients  (AUC: 0.81, 0.95, 0.94, respectively). Similarly platelets differentiated the middle, late MVD-recovered groups and MVD patients (AUC: 0.79,0.61, 0.90, respectively). Creatinine and lymphocytes were also suggested as potential biomarkers for MVD development. These findings provide novel insights into biological factors crucial for MVD management. Although all investigated biomarkers can be used to monitor MVD patients, our analyses highlight key biosignatures that can guide clinicians to track MVD progression and enable real-time decisions.